2005
DOI: 10.1103/physrevlett.94.218701
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization is Enhanced in Weighted Complex Networks

Abstract: The propensity for synchronization of complex networks with directed and weighted links is considered. We show that a weighting procedure based upon the global structure of network pathways enhances complete synchronization of identical dynamical units in scale-free networks. Furthermore, we numerically show that very similar conditions hold also for phase synchronization of nonidentical chaotic oscillators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
289
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(301 citation statements)
references
References 18 publications
9
289
0
Order By: Relevance
“…Motivated by the practical requirement and theoretical interest, numbers of scientists begin to study how to enhance the network synchronizability, especially for scalefree networks [41,42]. These methods keep the network topology unchanged, while add some weight into the system, thus the coupling matrix is changed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Motivated by the practical requirement and theoretical interest, numbers of scientists begin to study how to enhance the network synchronizability, especially for scalefree networks [41,42]. These methods keep the network topology unchanged, while add some weight into the system, thus the coupling matrix is changed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[6][7][8][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In particular, the study on controlling the dynamics of a network and guiding it to a desired state, such as, an equilibrium point or a periodic orbit of the network has become an interesting and important direction in this research field. 7,[18][19][20][22][23][24]26,27 It has been revealed that, in the process of controlling various networks, feedback control serves as a simple and effective approach for stabilization and synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades dynamics on network received a growing amount of interest [Dhamala et al, 2004;Zigzag et al, 2009;Choe et al, 2010;Chavez et al, 2005;Sorrentino and Ott, 2007;Albert et al, 2000;Kinzel et al, 2009;Lehnert et al, 2011a;Keane et al, 2012]. One of the central topics of dynamics on networks is synchronization [Strogatz and Stewart, 1993;Rosenblum et al, 1996;Pikovsky et al, 2001;Pecora and Carroll, 1998;Mosekilde et al, 2002;Wang and Chen, 2002;Arenas et al, 2006aArenas et al, , 2008Balanov et al, 2009;Omelchenko et al, 2010;Schöll, 2013].…”
Section: Dynamics On Networkmentioning
confidence: 99%
“…Previous research in the field of network science focused either on the construction of topologies [Rapoport, 1957;Erdős and Rényi, 1959;Watts and Strogatz, 1998;Albert and Barabasi, 2002;Newman, 2003;Boccaletti et al, 2006b] or on the dynamics on a network with fixed topology Dhamala et al, 2004;Chavez et al, 2005;Sorrentino and Ott, 2007;Zigzag et al, 2009;Choe et al, 2010;Kinzel et al, 2009;Lehnert et al, 2011a;Keane et al, 2012]. Recently, adaptive networks attracted a lot of interest as they bring these two aspects together: In such networks the topology evolves according to the state of the system while the dynamics on the network and thus the state is influenced by the topology [Gross and Blasius, 2008].…”
Section: Adaptive Networkmentioning
confidence: 99%
See 1 more Smart Citation